Aerodynamics of unconventional airfoils - Tee, Kok Heng. (2010)
This project investigated the lift characteristics of high lift low Reynolds number (Re) airfoil S1223 under low Re flow regime for Micro Air Vehicle (MAV) applications through numerical methods using FLUENT and experimentally via water tunnel aerodynamic testing. The project also explored the effects of a flap addition to the airfoil.